Ciudad Cayalá, a New Extension of Guatemala City - María Sánchez (INTBAU Spain, 2021)
In 2003, Estudio Urbano in partnership with master planner Leon Krier, proposed a new traditional town as an extension of Guatemala City: Ciudad Cayalá. Its goal is to create a humane, hospitable urban environment that fosters a strong sense of community, while generating local employment opportunities and a vibrant commercial and civic life. Paseo Cayalá is the first built quarter that is intended to serve as a model for future growth. It revives Guatemala’s unique architectural identity and offers a way of life radically different from the typically disconnected, car-oriented developments. The principle of mixed-use and programmatically-tuned architectural variety has laid the foundation for a robust emerging public realm. Paseo Cayalá celebrates local identity and has become a place of hope and happiness.